Beautiful Joe : an autobiography - Saunders, Marshall, 1861-1947. (Bedford, Mass. : Applewood Books, 1994)
A dog describes being mistreated by a cruel master but then later being taken in by a kind family.
Mode of access: Internet.
Keywords: Dogs -- Fiction